Pengaruh Persepsi Harga, Gaya Hidup, dan Sosial Media Marketing terhadap Minat Beli Pakaian Thrift di Kalangan Mahasiswa UNISMA - Haq, M Agung Izul; Widarko, Agus; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze people's buying interest in thrift clothing based on price perceptions, and whether thrift clothing has its own value compared to new clothing. This is relevant because currently many people consider consumption prices as part of a lifestyle in meeting individual needs, as well as its influence on the marketing of thrifty clothing on social media. This research used quantitative methods with the student population of the Islamic University of Malang and involved 96 respondents selected through purposive sampling techniques. Data was obtained from primary sources through distributing questionnaires and analyzed using SPSS version 25.0. The research results show that simultaneously or partially, Price Perception (X1), Lifestyle (X2), and Social Media Marketing (X3) have a positive effect on Purchase Interest (Y). Keywords: Price Perception, Lifestyle, Social Media Marketing, Purchase Intention, Thrift Clothes